2018
DOI: 10.1093/nutrit/nuy025
|View full text |Cite
|
Sign up to set email alerts
|

Maternal oversupplementation with folic acid and its impact on neurodevelopment of offspring

Abstract: Folic acid, a B vitamin, is vital for early neurodevelopment and is well known for its protective effect against neural tube defects. Various national health agencies worldwide recommend that women of childbearing age take approximately 0.4 to 1 mg of supplemental folic acid daily to reduce the risk of neural tube defects in offspring. Several countries have tried to promote folic acid intake through mandatory fortification programs to reduce neural tube defects. Supplementation combined with mandatory fortifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…36 However, concerns have been raised that higher doses of folate supplementation might be injurious and increase the risk of autism. 37 Because some ASMs interfere with folate levels or mechanisms (e.g., enzyme-inducing ASMs and lamotrigine), the dose for women taking ASMs might differ from that for the general population. Higher doses could be considered for women taking ASMs that interfere with folate or women with personal or family history of neural tube defects in pregnancies, but the safety of doses >4 to 5 mg/d has been questioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 However, concerns have been raised that higher doses of folate supplementation might be injurious and increase the risk of autism. 37 Because some ASMs interfere with folate levels or mechanisms (e.g., enzyme-inducing ASMs and lamotrigine), the dose for women taking ASMs might differ from that for the general population. Higher doses could be considered for women taking ASMs that interfere with folate or women with personal or family history of neural tube defects in pregnancies, but the safety of doses >4 to 5 mg/d has been questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Higher doses could be considered for women taking ASMs that interfere with folate or women with personal or family history of neural tube defects in pregnancies, but the safety of doses >4 to 5 mg/d has been questioned. 37 In addition, folic acid does not have the same metabolic pathway as folate. Folic acid requires hepatic conversion via methyl tetrahydrofolate dihydrofolate reductase (MTHFR) to be utilized, and the activity of hepatic dihydrofolate reductase varies greatly among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, women with epilepsy should be prescribed at least 0.4 mg/day since this is the recommended dose for women in general, as well as women with epilepsy according to some guidelines (Harden et al, 2009a). The fact that some AEDs can interfere with folate suggests that higher doses of folate might be required, but there have been concerns that folate, in particular at high dose, may increase the risk of cancer, cognitive impairment, and oral clefts (Frankenburg, 2009;Rozendaal et al, 2013;Morris et al, 2010;Murray et al, 2018). Some guidelines recommended that all women with epilepsy who are trying for pregnancy should start on folic acid at 5 mg daily, at least three months prior to pregnancy, and continue with the same dose throughout pregnancy (Wilson et al, 2007;NICE, 2012), however, evidence for an optimal periconceptional dose of folate in women with epilepsy taking AEDs remains inadequate.…”
Section: Folatementioning
confidence: 99%
“…Food fortification with FA is now routine in many countries and has reduced NTD rates [ 4 ]. However, recent concerns have been raised regarding high folate intake during pregnancy and lactation, since it has been estimated that 15–20% of pregnant women exceed recommended levels by more than four-fold due to food fortification and increased use of supplements [ 4 , 5 , 6 ]. Several epidemiological studies have shown that high FA intake can negatively impact motor, social and neurocognitive development in offspring [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent concerns have been raised regarding high folate intake during pregnancy and lactation, since it has been estimated that 15–20% of pregnant women exceed recommended levels by more than four-fold due to food fortification and increased use of supplements [ 4 , 5 , 6 ]. Several epidemiological studies have shown that high FA intake can negatively impact motor, social and neurocognitive development in offspring [ 5 , 6 ]. Animal studies have shown that DNA methylation and gene expression [ 7 , 8 , 9 , 10 , 11 ], brain fatty acid content [ 12 ], and neurotrophic factor levels [ 13 ] are altered in offspring brain by maternal FA supplementation.…”
Section: Introductionmentioning
confidence: 99%